solve the top eqn. for q
q=4-p
Now sub 4-p in for q in the second eqn.
4p +4-p = 1
3p+4=1
3p=-3
p=-1
q = 4 -( -1) = 5
2007-02-19 04:45:12
·
answer #1
·
answered by leo 6
·
0⤊
0⤋
You want to solve for one of the unknowns in the simplest equation.
Using p + q = 4, you can solve for q and get q = 4 - p.
By substitution, enter 4 - p in for q in the other equation:
4p + q = 1
4p + 4 - p = 1
3p + 4 = 1
3p = -3
p = -1
Now you have solved for p. You can now solve for q by putting your value for p back into one of the equations. I"m going to choose the most simple one:
p + q = 4
-1 + q = 4
q = 5.
2007-02-19 04:57:50
·
answer #2
·
answered by True_D 1
·
0⤊
0⤋
Solve the first equation for one of the variables:
p = 4 - q
Substitute this value into the second equation and solve for the other variable:
4(4 - q) +q = 1
16 - 4q + q = 1
16 - 3q = 1
3q = 15
q = 5
Substitute this value back into the first equation and solve for the first variable:
p + 5 = 4
p = 4 - 5
p = -1
2007-02-19 04:48:42
·
answer #3
·
answered by T 5
·
0⤊
0⤋
1) p+q = 4 ISOLATE ONE OF THE VARIABLES.
-q -q
2) p = 4-q
3) 4(4-q) + q = 1 PLUG IN THE P (which is already equal to 4-q)
4) 16-4q+q = 1 DISTRIBUTE the 4 into the parenthases.
5) 16-3q = 1 ADD THE COMMON VARIABLES.
6) -3q = -15 DIVIDE by -3 on both sides.
7) q = 5 Now you have solved for q.
Now all you have to do is plug in 5 for q to solve for p. I hope I helped and didn't just confuse you more. I tend to do that when explaining things. =)
2007-02-19 05:03:57
·
answer #4
·
answered by Alli 3
·
0⤊
0⤋
p+q= 4 means q = 4-p (a)
you put this value of q in the second equation
4p+4-p =1
3p=-3 p=-1 and in a you find q=5
result p = -1 q=5
2007-02-19 04:46:46
·
answer #5
·
answered by maussy 7
·
0⤊
0⤋
So in the top problem solve for p, you won't eliminate any variables yet. p= -q+4
Now where ever you see p in the next equation put in -q+4 in parenthesizes so now it's 4( -q+4)+q=1
Distribute the 4 into the parenthesizes - 4q+16+q=1
Solve for q... ------> q=5
Put 5 in for q in the first equation and solve for p.... p+5=4
So p = -1 and q = 5
2007-02-19 04:55:58
·
answer #6
·
answered by blah_girl2002 2
·
0⤊
0⤋
Start with the first equation, and rewrite it in terms of p or q:
p = 4-q (rewritten in terms of q)
Since we now know p in terms of q, substitute the expression 4-q for p in the second equation:
4(4-q)+q = 1 and solve for q
q = 5
Now plug q into the first equation and solve for p:
p+5 = 4
p = -1
That's it!
2007-02-19 04:50:37
·
answer #7
·
answered by Roger L 3
·
0⤊
0⤋
You solve the first equation for q
p+q=4
-p__-p
q=4-p
then you plug in that equation for Q in the second equation
4p+(4-p)=1
4p+4-p=1
solve
3p=-3
p=-1
then you plug p=-1 into the first equation
-1+q=4
solve
q=5
plug it in to check
2007-02-19 04:47:32
·
answer #8
·
answered by Briar 4
·
0⤊
0⤋
p+q = 4 subtract p from both sides
q=4-p
4p+q = 1 substitute 4-p for q
4p+4-q=1 combime like terms
3p+4=1 subtract 4 from each side
3p=-3 divide both sides by 3
p=-1
q=4-p substitute -1 for p
q=4-(-1)
q=5
(-1, 5)
2007-02-19 04:46:03
·
answer #9
·
answered by yupchagee 7
·
0⤊
0⤋
p+q =4: q = 4-p (sub this into the second equation for q
4p+q =1
4p + 4-p = 1
3p +4 =1
3p = -3
p = -1
q = 4-(-1)
q = 5
(-1,5)
2007-02-19 04:45:51
·
answer #10
·
answered by lizzie 3
·
0⤊
0⤋